2020
DOI: 10.1155/2020/7414050
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Depression and Diabetes Distress in Type 2 Diabetes in Kuwait

Abstract: This study is aimed at describing the prevalence of and risk factors for depression and diabetes distress in people with type 2 diabetes and whether depression and distress are independently associated with worse biomedical outcomes. The study was of cross-sectional design. The setting was the Dasman Diabetes Institute, Kuwait. The Patient Health Questionnaire-9 (PHQ-9) was used to measure the prevalence of depression, defined as a score≥10 (depression caseness). The Problem Areas in Diabetes (PAID) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 26 publications
4
22
2
1
Order By: Relevance
“…In the present study subjects with high monthly income were more likely to accept the vaccine against COVID-19 infection. This is in line with previous studies (28)(29)(30). In the present study, the presence of self-reported health status (having chronic medication) was associated with higher acceptance of the COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study subjects with high monthly income were more likely to accept the vaccine against COVID-19 infection. This is in line with previous studies (28)(29)(30). In the present study, the presence of self-reported health status (having chronic medication) was associated with higher acceptance of the COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 93%
“…Other factors affecting patients' health literacy included exercising, duration of hypertension and family history of hypertension. Many studies showed that there is association between bad lifestyle, low level of health literacy and low control of hypertension [25,[30][31][32][33]. Low level of health literacy means that patients didn't comprehend the needed information regarding the importance and how to control the disease, as exercising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Patient Health Questionnaire-9 (PHQ-9) with a 9-question depression scale, was used to screen for the presence and severity of depressive symptoms according to the Diagnostic and Statistical Manual of Mental Disorders-IV criteria (DSM-IV) ( 10 ). Subjects were asked to respond to each symptom by rating the best statement applied over the past 2 weeks, using a score from zero to three (ranging from “not at all” = zero, “several days” = one, “more than half the days” = two, or “nearly every days” = three).…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review found RF to be associated with a negative impact to mental wellbeing [42]. People with pre-existing feelings of depression might also experience poorer glycaemic control when fasting during Ramadan [43]. The changes that occur to energy intake during RF has also been linked to fatigue, deteriorated mood and greater irritability [44].…”
Section: Effects Of Rf On Mental Wellbeingmentioning
confidence: 99%